In my life - Lamasan, Olivia M.; Star Recording, Inc. (Firm). (Quezon City Star Recording, 2009)
Shirley is a woman who wants to be in control of everything. Working as a librarian in a public school, a firm "Sshhh" from her makes the students tremble in fear. but in her family, her unwarranted intervention in the lives of her children keeps her emotionally detached from them. Realizing that she has lost the command she once had, she goes to New York to reunite with her estranged gay son Mark.
Summary taken from cover
Directed by Olivia M. Lamasan.
Vilma Santos, John Lloyd Cruz, Luis Manzano
Keywords: Feature Films